Faktor-Faktor yang Mempengaruhi Kinerja Perawat di Rumah Sakit Wilayah Kerja Kecamatan Batam Kota - Novi Yulianti; Susanti Susanti (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Nurse performance is a key indicator of service quality and patient safety in hospitals. Performance is influenced by various individual and organizational factors, such as job satisfaction, work motivation, managerial support, and workload. Batam Kota District has a high level of patient mobility, thus requiring optimization of nursing staff performance. This study aims to analyze the factors that influence nurse performance in hospitals within the Batam Kota District. This study used a quantitative analytical design with a cross-sectional approach. A sample of 72 nurses was selected using purposive sampling technique from a total population of 260 nurses. Data were collected using a Likert scale questionnaire that has been tested for validity and reliability. Data analysis included univariate analysis, Pearson correlation test, and multiple linear regression with a significance level of p < 0.05. The results showed that job satisfaction (β = 0.284; p = 0.012), work motivation (β = 0.321; p = 0.005), and managerial support (β = 0.216; p = 0.031) had a positive and significant effect on nurse performance. Workload had a negative and significant effect on performance (β = -0.198; p = 0.044). Work motivation was the most dominant factor. The simultaneous regression model was significant (F = 18.624; p < 0.001) with an Adjusted R² of 0.594, meaning 59.4% of the variation in nurse performance could be explained by the variables studied. Nurse performance was significantly influenced by work motivation, job satisfaction, managerial support, and workload. Efforts to improve the quality of nursing services need to be focused on strengthening the motivation system, increasing job satisfaction, optimizing managerial supervision, and managing workload proportionally.